2014
DOI: 10.1080/02671522.2014.919523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kindergarten retention for at-risk children’s mathematics development

Abstract: When a child does not seem to be ready for primary school, a popular practice is to grant the child more time by letting it repeat kindergarten. However, previous quasi-experimental research demonstrated negative, though diminishing, effects of kindergarten retention on academic learning during the first years of primary school. The present study extends the existing evidence by addressing children's post-treatment school trajectories. Analysing data from a large-scale longitudinal study, we find that, on aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
5
1
Order By: Relevance
“…A recent generation of studies has used techniques to adjust for pre-treatment differences. Recent studies using same-age comparisons have found that at-risk children may benefit more from receiving intellectual challenges that are offered in a higher grade (Goos, Van Damme, Onghena, Petry, & De Bilde, 2013;Hong & Yu, 2007;Hong & Raudenbush, 2005;Hong & Raudenbush, 2006;Vandecandelaere et al, 2015a;Vandecandelaere, Vansteelandt, De Fraine & Van Damme, 2015b;Wu et al, 2008a;Wu, West & Hughes, 2008b). Recent research using same-grade comparisons has demonstrated that grade repeaters, compared to their younger grade-mates, score better in math during the retention year.…”
Section: Empirical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…A recent generation of studies has used techniques to adjust for pre-treatment differences. Recent studies using same-age comparisons have found that at-risk children may benefit more from receiving intellectual challenges that are offered in a higher grade (Goos, Van Damme, Onghena, Petry, & De Bilde, 2013;Hong & Yu, 2007;Hong & Raudenbush, 2005;Hong & Raudenbush, 2006;Vandecandelaere et al, 2015a;Vandecandelaere, Vansteelandt, De Fraine & Van Damme, 2015b;Wu et al, 2008a;Wu, West & Hughes, 2008b). Recent research using same-grade comparisons has demonstrated that grade repeaters, compared to their younger grade-mates, score better in math during the retention year.…”
Section: Empirical Examplementioning
confidence: 99%
“…A second issue in grade retention research is that retainees and promoted children differ with regard to a large number of variables. For example, compared to children who are promoted to first grade, children who are retained in kindergarten are on average younger, have lower scores in mathematics, language and psychosocial skills, speak more often a foreign language, and have a lower socio-economic status (Vandecandelaere, Schmitt, Vanlaar, De Fraine, & Van Damme, 2015a). This raises concerns that the observed effects of grade retention may be confounded.…”
mentioning
confidence: 99%
“…We showed that the reason why the study by Goos et al (2013) came to different conclusions is due to a strong bias between the groups of repeaters and nonrepeaters. The other studies carried out on the same dataset (Vandecandelaere, Schmitt, Vanlaar, De Fraine, & Van Damme, 2015;Vandecandelaere et al, 2016a;Vandecandelaere et al, 2016b), just like the study by Goos et al, only examined the effects of grade retention in the beginning of primary school (third kindergarten until second grade). Given the methods used in these studies, propensity score matching and marginal structural models, the conclusions of these authors are not very different from the results we presented using marginal structural models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For the sake of an illustrative comparison, we compare in Table 1 the results of the current study (Study 2) with the results of an earlier study in which we used the same dataset and addressed the same research question but which entailed more assumptions and ignored some of the complexities originating from the presence of time-varying confounders (see Vandecandelaere, Schmitt, De Fraine & Van Damme, 2015). Table 1 and modelling time as a multivariate response relaxed some of the assumptions.…”
Section: Reducing Reality To Disentangle the Truth?mentioning
confidence: 95%
“…Future simulation studies might give more insight into the sources of these differences. Table 1 Contrasts, standard errors and effect sizes in study 1 (Vandecandelaere et al, 2015) and study 2 (Vandecandelaere et al, 2016) …”
Section: Reducing Reality To Disentangle the Truth?mentioning
confidence: 99%